The Role of Financial Ratios in Bankruptcy Prediction: An Empirical Study Using Contemporary Financial Data - Abdulrahman, Murtala; AbdulRahman Bala, Sani (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Corporate bankruptcy poses considerable risks to various stakeholders. This study investigated contemporary issues in predicting corporate bankruptcy in the non-financial public companies in the United States, using five key financial ratios: Cash Flow to Total Liabilities (OANCFLT), Net Income to Total Sales (NIREVT), Total Liabilities to Total Assets (LTAT), Total Current Assets to Total Current Liabilities (ACTLCT), and Total Assets to Total Sales (ATREVT). Utilizing a multivariate logistic regression model and monthly data from 2017 to 2021, this research examined the predictive power of these ratios and their effectiveness in identifying early signs of corporate failure. The findings underscore the importance of certain financial ratios, particularly LTAT with 80% predictive power in the year before bankruptcy and OANCFLT at 65% and statistically significant with t-values of -2.85, offering valuable insights for stakeholders aiming to mitigate financial risks.